Skewness in the literature on infectious livestock diseases in an emerging economy - the case of Vietnam - Rajala, E.; Hu Suk Lee; Nguyen Hoai Nam; Chu Thi Thanh Huong; Hoang Minh Son; Wieland, Barbara; Magnusson, Ulf (Cambridge University Press, 2021)
Livestock production has increased in many emerging economies, but productivity is often substantially impaired by infectious diseases. The first step towards improved livestock health and productivity is to map the presence of livestock diseases. The objective of this review was to summarize studies conducted on such diseases in an emerging economy, Vietnam, and thereby identifying knowledge gaps that may inform the design of surveillance and control programs. Few studies were found to evaluate the distribution of infectious livestock diseases other than avian influenza. Also, many regions with dense livestock populations had received little attention in terms of disease investigation. A large proportion of the studies dealt with zoonoses and food-borne infections which might be due to funding agencies priorities. On the contrary, studies targeting infections that affect livestock and their productivity were few. We think that this limitation in scientific reports on infectious diseases that only affect livestock productivity is a common phenomenon in low and lower middle income countries. More science-based data on such diseases would help policymakers to prioritize which livestock diseases should be subject to animal health programs aimed to support rural livelihoods and economic development.